Yehuda Halevi poetry and pilgrimage - Yahalom, Yosef 1941- (The Hebrew University Magnes Press, 2009)
Yehuda Halevi: Poetry and Pilgrimage follows the life story of the greatest Hebrew poet of medieval times from his first publication in Christian Toledo to his heroic journey toward Zion from Muslim Spain. The description is based, for the first time, on the entire collection of his poetry- The Diwan, which was edited and reedited between East and West at every important crossroad of his life. This in turn is done through comparison to autographical letters and contemporary correspondence discovered and collected over the past 50 years in the Cairo Geniza collections. Documentary material and Literary works, which were shun behind the iron wall in The Russian National Library in St. Petersburg, are woven for the first time into one, enabling us to examine closely the intricate relationship between old Jewish traditions and the ideological heritage associated with Halevi's innovative writings in prose and in poetry. Confronting Halevi's "Zion, will thou not ask"? opens the study which is mainly concerned with the story of Halevi's odyssey from Christian to Muslim Spain and eventually to Egypt, including the epic quest to the beloved yet fatal Zion.--Cover